Sliding-mode control of induction motor based on inverse decoupling. (1st January 2012) - Wu, Qinghui
A classic Sliding-Mode Controller (SMC) for a high-performance induction motor drive system based on inverse decoupling control is developed in this paper. The proposed scheme consists of a decoupling controller (as inner loop) and a slidingmode speed controller (as outer loop). First, in order to eliminate the coupling effect between the stator flux and the electromagnetic torque, a general composite system based on inverse model, which is decoupled into two separate linear subsystems, is constituted by nonlinear state feedback. Second, a sliding-mode speed controller, in which the use of simple linear equations to abstain the control law make it easy to understand and implement, is proposed to enhance robustness in the presence of parameters and disturbance uncertainties. Third, in order to reduce the inherent chattering, the parameters in SMC are reasonable to be designed by Lyapunov's theory under satisfying some robustness. Comparative simulation results shows the feasibility of the proposed method, obtaining good speed control performance with robustness, quickness and no-overshoot while overcoming classic PID drawbacks.